A Parkinson's disease CircRNAs Resource reveals a link between circSLC8A1 and oxidative stress. Issue 9 (26th July 2020) - Hanan, Mor; Simchovitz, Alon; Yayon, Nadav; Vaknine, Shani; Cohen‐Fultheim, Roni; Karmon, Miriam; Madrer, Nimrod; Rohrlich, Talia Miriam; Maman, Moria; Bennett, Estelle R; Greenberg, David S; Meshorer, Eran; et al.
Abstract: Circular RNAs (circRNAs) are brain‐abundant RNAs of mostly unknown functions. To seek their roles in Parkinson's disease (PD), we generated an RNA sequencing resource of several brain region tissues from dozens of PD and control donors. In the healthy substantia nigra (SN), circRNAs accumulate in an age‐dependent manner, but in the PD SN this correlation is lost and the total number of circRNAs reduced. In contrast, the levels of circRNAs are increased in the other studied brain regions of PD patients. We also found circSLC8A1 to increase in the SN of PD individuals. CircSLC8A1 carries 7 binding sites for miR‐128 and is strongly bound to the microRNA effector protein Ago2. Indeed, RNA targets of miR‐128 are also increased in PD individuals, suggesting that circSLC8A1 regulates miR‐128 function and/or activity. CircSLC8A1 levels also increased in cultured cells exposed to the oxidative stress‐inducing agent paraquat but were decreased in cells treated with the neuroprotective antioxidant regulator drug Simvastatin. Together, our work links circSLC8A1 to oxidative stress‐related Parkinsonism and suggests further exploration of its molecular function in PD. Synopsis: In human brains, circRNA levels are region specific and inversely correlate to editing. In PD circRNAs are reduced in SN and accumulation correlation with age is lost. CircSLC8A1 increases in PD and oxidation, is bound to Ago2 and sponges miR128 targets, modulating neuronal survival and aging. CircRNA levels to be brain region‐specific and are inversely correlate to the editing of Alu repeats. In the healthy substantia nigra (SN), circRNAs accumulate in an age‐dependent manner, but in the Parkinson's Disease (PD) SN, this correlation is lost and the total number of circRNAs is reduced. CircSLC8A1 levels increase in the SN of PD individuals and in cultured cells exposed to the oxidative stress‐inducing agent Paraquat. CircSLC8A1 carries 7 binding sites for miR‐128 and is strongly bound to Ago2. Indeed, RNA targets of miR‐128 are also increased in PD individuals, suggesting that circSLC8A1 regulates miR‐128 function and/or activity. Abstract : In human brains, circRNA levels are region specific and inversely correlate to editing. In PD circRNAs are reduced in SN and accumulation correlation with age is lost. CircSLC8A1 increases in PD and oxidation, is bound to Ago2 and sponges miR128 targets, modulating neuronal survival and aging.